Plasma Modified MoS2 Nanoflakes for Surface Enhanced Raman Scattering. Issue 6 (13th February 2014) - Sun, Linfeng; Hu, Hailong; Zhan, Da; Yan, Jiaxu; Liu, Lei; Teguh, Jefri S.; Yeow, Edwin K. L.; Lee, Pooi See; Shen, Zexiang
<x xml:space="preserve">Abstract</x> Though the SERS effect based on pristine MoS2 is hardly observed, however, the plasma treated MoS2 nanoflakes can be used as an ideal substrate for surface enhanced Raman scattering. It is proved that the structural disorder induced generation of local dipoles and adsorption of oxygen on the plasma treated MoS2 nanosheets are the two basic and important driven forces for the enhancement of Raman signals of surface adsorbed R6G molecules. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>